A Study On The Use Of Mind Mapping In Teaching Writing - Fani Nurhasanah; Konder Manurung; Agussatriana Agussatriana (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research aims to investigate the use of mind mapping as a teaching technique to enhance students’ writing skills in descriptive text. Using a qualitative library research approach, data were gathered from secondary sources, including theses, journals, and articles published between 2012 and 2024. The analysis focused on identifying teaching procedures, outcomes, and effectiveness across five selected studies. The findings indicate that mind mapping significantly improves students’ ability to generate, organize, and connect ideas, resulting in more coherent and creative descriptive texts. It also enhances vocabulary, grammar, and students’ motivation to write. Across the reviewed studies, post-test scores consistently showed substantial improvement, demonstrating the technique’s effectiveness in both secondary and tertiary educational contexts. Mind mapping’s use of colors, images, and keywords makes the writing process more engaging and accessible, supporting active learning and critical thinking. Based on these findings, the study recommends that English teachers adopt mind mapping as a strategy to improve descriptive writing skills and suggests further exploration of its application to other genres of writing.